Epistemologi Lokal Masyarakat Desa Nemberala, Rote Barat dalam Kegiatan “Makameting” - Gloria Bayu Nusa Prayuda; Agung Harijoko (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
This study aims to examine epistemological elements in the "Makameting" tradition of the people of Nemberala Village, West Rote. Makameting is an activity of the coastal community of Rote in fulfilling their daily needs, by collecting food on the beach when the sea water recedes. The Makameting tradition has been carried out for years, it has become a habit in the daily life of the Rote people. This study uses a descriptive--nterpretative method, with literatures and interview with locals as reference for writing. The results show that there are epistemic elements that provide situational preconditions for makameting activities, such as biological, geographic and cultural elements. The biological in makameting is how society as beings who have agency to fulfill their life needs and to preserve their environment, the geographical element found is how the coastal landscape determines the social dynamics of the community, while the cultural element is how the sea is viewed anthropomorphically and the daily life of makameting itself.